Antiviral effect of mangiferin and isomangiferin on herpes simplex virus - Zheng Min-shi; Lu Zong-yi (Acta Pharmacologica Sinica, 2016)
Using tissue culture techniques the present study assured us of the merits of mangiferin and isomangiferin in the antiviral action against HSV-1. Utilizing 4 main patterns for evaluating drug effectiveness (ie intratube drug-on-virus direct action, simultaneous addition of drug-virus-inoculum to cell bottle, virus inoculation preceding drug addition, and drug addition followed by virus inoculation), it was readily found by logarithm determination of HSV-I inhibition that isomangiferin was superior to such control drugs as acyclovir, idoxuridine, and cyclocytidine in logarithm by 0.27-0.50, and that mangiferin was lower than isomangiferin in logarithm by 0.53. The average plaque reduction rates of mangiferin and isomangiferin were 69.5% and 56.8%, respectively. All in all, the antiviral effect of mangiferin and isomangiferin was attributed presumably to their capability to inhibit virus replication within cells.